Kesavan Veluthat and Donald R. Davis, Jr. (Ed.) Irreverent History. Essays in Honour of M.G.S. Narayanan. Delhi: Primus Books. 2014, 328pp, ISBN: 978-93-84082-14-7 - Lidia Sudyka (Ksiegarnia Akademicka Publishing, 2021)
Kesavan Veluthat and Donald R. Davis, Jr. (Ed.) Irreverent History. Essays in Honour of M.G.S. Narayanan. Delhi: Primus Books. 2014, 328pp, ISBN: 978-93-84082-14-7—Reviewed by Lidia Sudyka (Jagiellonian University)